CLASSIFICATION OF VECTOR CONVERTERS - Zayets, Serhii; Kyrychuk, Yury; Nazarenko, Natalia (Sworld-Us Conference proceedings, 2023)
In the work, the classification of vector converters of mechanical quantity is performed. The classification is made depending on the types of sensitive elements, schemes of construction of transducers and the number of measuring projections, transducers